1985
DOI: 10.1177/101269028502000109
|View full text |Cite
|
Sign up to set email alerts
|

Who Rules Sport? Gender Divisions in the Power Structure of British Sports Organisations from 1960

Abstract: The increase in participation of women in sport has not been matched by a similar increase in the involvement of women as administrators and decision-makers. In all British sports organisations studied, women remained underrepresented at administrative, controlling and decision-making levels. Analysis of trends since 1960 revealed little change in the percentage of women occupying positions of power. Women's power has been effectively lessened since the 1960s with the move towards a more professionalised and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 1 publication
0
28
0
2
Order By: Relevance
“…In the realm of sport, although a growing body of studies has emerged to examine and understand women's underrepresentation in sport governance (Claringbould & Knoppers, 2007Fasting, 2000;Hall, Cullen, & Slack, 1989;Hovden, 2000;McKay, 1992;Ottesen, Skirstad, Pfister, & Habermann, 2010;Pfister & Radtke, 2009;Shaw, 2006;Shaw & Penney, 2003;Shaw & Slack, 2002;Sibson, 2010;Skirstad, 2009;White & Brackenridge, 1985), research into the impact of gender targets and quotas is rare. The aim of this article is to investigate the impact of gender quotas on gender equality in sport governance.…”
mentioning
confidence: 97%
“…In the realm of sport, although a growing body of studies has emerged to examine and understand women's underrepresentation in sport governance (Claringbould & Knoppers, 2007Fasting, 2000;Hall, Cullen, & Slack, 1989;Hovden, 2000;McKay, 1992;Ottesen, Skirstad, Pfister, & Habermann, 2010;Pfister & Radtke, 2009;Shaw, 2006;Shaw & Penney, 2003;Shaw & Slack, 2002;Sibson, 2010;Skirstad, 2009;White & Brackenridge, 1985), research into the impact of gender targets and quotas is rare. The aim of this article is to investigate the impact of gender quotas on gender equality in sport governance.…”
mentioning
confidence: 97%
“…Senior managerial work in most organizations, including that in sport, is still primarily a male domain (Acosta and Carpenter 2006;Claringbould 2006;Hughes 2004;Lapchick 2006). Researchers who have focused on the skewed gender ratio of the number of executive directors/senior managers in sport organizations have looked at ways in which these individuals explain their lack of women colleagues and/or have explored individual differences between men and women athletic directors (Fitzgerald et al 1994;Hoeber and Frisby 2001;Sagas and Cunningham 2004;Whisenant et al 2002;White and Brackenridge 1985). Shaw and Frisby (2006) however, have shown that gender not only shapes identities but is an axis of power that also plays an influential role in interactions, structures, and processes of sport organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Men continue to hold virtually all the key positions within the international and national sport federations throughout the world and on the International and National Olympic Committees (IOC, NOG) as well (Grant, 1984;Simri, 1981;Theberge, 1984;White & Brackenridge, 1985). As reported by Berlioux (1981), in 1974 only one woman held the position of president of a NOC or national and international sports federations.…”
Section: The Trend Ofunderrepresentationmentioning
confidence: 84%
“…Women are still underrepresented as leaders in the organization of sport on both national and international levels (Acosta & Carpenter, 1985a;Grant, 1984;Holmen & Parkhouse, 1981;Simri, 1981;Theberge, 1984;White & Brackenridge, 1985).…”
Section: The Trend Ofunderrepresentationmentioning
confidence: 98%